LOCAL WISDOM OF THEKELAN FARMERS IN GETASAN DISTRICT, SEMARANG REGENCY - Muhammad Ulil Ilmi; Wulan Sumekar; Agus Subhan Prasetyo (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
The local wisdom of farmers is created based on the long experience of predecessors related to the problems of the agricultural system and the environment to gain maximum results without destroying the balance of nature. The local wisdom of farmers is closely related to traditional perspectives, obedience to local customs and culture, and knowledge of virtues related to ethics and morals. One of the people in Indonesia who do farming activities with the implementation of local wisdom is the Thekelan farmer. They apply local wisdom in farming according to the teachings passed down from generation to generation by their ancestors. The location of Thekelan farmers is in Thekelan Village, Getasan District, Semarang Regency. For Thekelan farmers, being a farmer is full of dignity, as evidenced in various traditional rituals expressing gratitude for their profession. From the point of view of the agribusiness subsystems, local wisdom still applied by Thekelan farmers by the utilization of livestock waste, application of four types of intercropping system, and doing traditional pamongan ceremonies with offerings in the form of “thowok” as a form of offering and gratitude to nature.